Modified Xiao-Qing-Long-decoction prevents inflammation and promotes Nur77 expression in mice with acute respiratory distress syndrome by inhibiting HDAC7 expression - Qing Zhang; Yafen Liu; Lu Jiang; Dongdong Yang (Pharmaceutical Biology)
Context Modified Xiao-Qing-Long-decoction (MXQLD) is believed to have the potential to alleviate lung diseases.Objective We explored the effects and mechanisms of MXQLD in acute respiratory distress syndrome (ARDS).Materials and methods Thirty male C57BL/6 mice were randomized into sham (distilled water), model (distilled water), MXQLD (1 g/kg MXQLD), DEX (distilled water + 0.7 mg/kg dexamethasone), MXQLD + oe-HDAC7 (HDAC7 over-expression + 1 g/kg MXQLD) groups. Except for HDAC7 over-expression on day 0 and dexamethasone injection on day 12, all treatments were administered every two days from day 0 to day 10. On day 12, except for the sham group, all mice underwent cecal ligation and puncture surgery to establish ARDS models. After surgery, pulmonary functions, protein concentration of bronchoalveolar lavage fluid (BALF) and lung tissue morphology in mice were detected. Furthermore, pro-inflammatory cytokine concentrations (IL-6, IL-1β, and TNF-α) in BALF supernatant and serum were quantified. Additionally, HDAC7, Nur77, ZO-1, occludin, and claudin protein expressions were detected.Results MXQLD treatment improved pulmonary functions and alleviated lung injury for ARDS mice. Furthermore, MXQLD treatment decreased protein concentration in BALF, and inhibited pro-inflammatory cytokine release in BALF supernatant and serum for ARDS mice. Additionally, MXQLD treatment down-regulated HDAC7 expression, but up-regulated Nur77, ZO-1, occludin, and claudin expressions for ARDS mice. Importantly, the preventive effects of MXQLD in ARDS mice were reversed by HDAC7 over-expression.Discussion and conclusion MXQLD may prevent inflammation and promote Nur77 expression in ARDS by inhibiting HDAC7 expression, indicating that MXQLD may be a promising drug for preventing ARDS.